2017
DOI: 10.1590/0104-07072017006250015
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Competencies: Identifying Gaps in Managerial Nursing Training

Abstract: Objective: mapping necessary competencies in managerial nursing training.Method: a cross-sectional study conducted between March and June 2013 with 258 students from three Higher Education Institutions of a municipality in the South of Brazil.Results: mapping made it possible to identify necessary competencies for managerial nursing training, including those acquired and gaps. The relative majority of the students considered having the right attitude to act as a nurse in the managerial dimension; however, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
0
12
0
6
Order By: Relevance
“…In this way, the individual act does not have more space and the systemic view becomes more and more necessary. Therefore, the leader with systemic view must possess negotiation skills and know how to manage conflicts in order to maintain a good relationship among team members (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the individual act does not have more space and the systemic view becomes more and more necessary. Therefore, the leader with systemic view must possess negotiation skills and know how to manage conflicts in order to maintain a good relationship among team members (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out on the managerial training of nurses that investigated the fields of: knowledge, skills and attitudes revealed that the skills of communication, leadership and permanent education present deficits when considered the fields abilities and attitudes needing to be still best explored in undergraduate (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The DCNs are the guiding axis for the pedagogical projects of course, glimpsing the minimum content for the formation and notes on the professional profile, geared towards generalist, critical, reflexive and humanistic formation, based on scientific rigor and ethics. 23 Health and administrative and managerial competences reflect knowledge, know-how and attitudes, identified as the three fields of competences, 24 as elements to be developed within the scope of training.…”
Section: Discussionmentioning
confidence: 99%